PENGARUH PEMBERIAN EKSTRAK ETANOL DAUN SIRIH MERAH (Piper Crocatum Ruiz & Pav) TERHADAP EKSPRESI GLUKOSA TRANSPORTER 2 PADA HATI DAN PANKREAS YANG DIINDUKSI STREPTOZOTOCIN-NIKOTINAMIDA - Wisnu Kusuma, Eka; Herowati, Rina; Nurrochmad, Arief (Jurnal Farmasi (Journal of Pharmacy), 2017)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia, decreased expression of GLUT-2 in pancreatic, and increased expression of GLUT-2 in liver. Red betel leaf seed is useful for treatment of diabetes. This study aims to determine the effect of antihyperglycemic, increased expression of GLUT-2 in pancreas, and decrease in liver of the red betel leaf ethanol extract in STZ-NA induced rats. This research used 25 male white wistar rats, which randomly divided into five groups, normal control, negative control, positive control, EEDSM dose of 50 mg/kg bw and 100 mg/kg bw. Induced STZ-NA days 0, measured glucose levels next day 5 and treated were for 14 days. Measured parameters were GLUT-2 expression in pancreas and liver. The results showed that EEDSM for 14 days qualitatively able to increase the expression of GLUT-2 in pancreatic cells with those in the normal control, negative control, positive control, EEDSM 50 mg/kg bw, and 100 mg/kg bw respectively to 100%, 32,31%, 67,67%, 52,73% and 60,01%. EEDSM qualitatively able to reduce the expression of GLUT-2 in liver cells with those in the normal control, negative control, positive control, EEDSM 50 mg/kg bw, and 100 mg/kg bw respectively to 13,21%, 100%, 52,05%, 87,08%, dan 78, 09%.